The Effect of Compensation and Work Motivation on Performance with Leadership Style as Moderator on Employees of the Secretariat of the Regional People's Representative Board of East Java Province - Asokawati, Dewa Ayu Karina; Budiyanto, Budiyanto; Khuzaini, Khuzaini (Accounting Department,, 2023)
Purpose—This research examines how compensation and work motivation impact employee performance at the Secretariat of the Provincial Legislative Council's Representative Board of East Java Province. Additionally, it explores the role of leadership style as a moderating factor in these relationships. Design/methodology/approach — The study employs moderated regression analysis to assess the relationships between compensation, work motivation, and employee performance, with leadership style as a moderating variable. The sampling technique used is saturated sampling, involving all 163 population members as respondents to ensure comprehensive data collection and analysis. Findings — The research findings indicate that both compensation and work motivation positively and significantly affect employee performance. However, the moderating effect of leadership style on the relationships between compensation and employee performance and between work motivation and employee performance was found to be weak. Practical implications — Organizations should continue to focus on improving compensation and work motivation strategies to enhance employee performance. While leadership style may not significantly moderate these relationships in this context, it remains essential for creating a supportive work environment. Further investigation into different leadership styles or additional factors might provide more insights into strengthening the moderating effect. Originality/value — This study provides valuable insights into the impact of compensation and work motivation on employee performance in a specific governmental context. It also contributes to understanding the role of leadership style as a moderating variable, highlighting areas for future research and practical applications in managing employee performance.